In situ scanning–digital image correlation for high-temperature deformation measurement of nickel-based single crystal superalloy. (17th May 2021) - Xie, Hongfu; Wang, Jie; Wang, Zhen; Zhao, Chong; Liang, Jiecun; Li, Xide
Abstract: In situ microscopic observation and measurement of deformations for advanced hot-section materials at high-temperature is helpful in understanding their failure mechanisms. Scanning electron microscopy (SEM) and a digital image correlation (DIC) method are combined to capture the failure process. This article reports an in situ high-temperature testing system which can heat the specimen up to 1000 °C and provide clear images simultaneously. The Al2 O3 nanoscale particles are developed as high-temperature deformation carriers in SEM–DIC, which are suitable for high-temperature samples with significant advantages of stability, high image contrast and without shedding or melting up to 1000 °C. High-temperature tensile and creep properties of a nickel-based single crystal superalloy (NBSCS) at 750 °C were investigated using this system. In addition, a scanning–DIC (S–DIC) method, which avoids errors introduced by conventional DIC methods, was used to calculate full-field dynamic displacement and strain of high-temperature NBSCS samples. Analysis of the strain fields show that the strain concentrations are generally at the positions of crack initiation or propagation, and the creep cracks interact with each other through the strain field. Finally, the crack opening displacement is obtained using the virtual extensometer.